2020
DOI: 10.3390/ijms21082761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on Protein Damage Induced by Rotenone in Dopaminergic PC12 Cells

Abstract: Oxidative stress is considered to be a key factor of the pathogenesis of Parkinson’s disease, a multifactorial neurodegenerative disorder characterized by reduced dopaminergic neurons in the substantia nigra pars compacta and accumulated protein aggregates. Rotenone is a worldwide-used pesticide that induces the most common features of Parkinson’s by direct inhibition of the mitochondrial complex I. Rotenone-induced Parkinson’s models, as well as brain tissues from Parkinson’s patients, are characterized by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Evidence in recent years supports the efficacy of curcumin in PD. In both in vitro and in vivo models of PD curcumin could prevent oxidative stress toxicity by reducing the production of ROS and malondialdehyde and restoring GSH levels [123][124][125] which shields against alpha-synuclein-induced toxicity in the brain [123]. More specifically, antioxidative and anti-apoptotic activity of curcumin has been reported in in vitro studies, indicating the neuroprotective effect of curcumin on dopaminergic neurons [124,125].…”
Section: Neuroprotective Effect Of Curcuminmentioning
confidence: 99%
“…Evidence in recent years supports the efficacy of curcumin in PD. In both in vitro and in vivo models of PD curcumin could prevent oxidative stress toxicity by reducing the production of ROS and malondialdehyde and restoring GSH levels [123][124][125] which shields against alpha-synuclein-induced toxicity in the brain [123]. More specifically, antioxidative and anti-apoptotic activity of curcumin has been reported in in vitro studies, indicating the neuroprotective effect of curcumin on dopaminergic neurons [124,125].…”
Section: Neuroprotective Effect Of Curcuminmentioning
confidence: 99%
“…Curcumin scavenges biological radicals including superoxide anion, hydrogen peroxide, 1,1-diphenyl-2-picryl-hydrazyl free radical, 2,2′-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) radical, and N , N -dimethyl- p -phenylenediamine dihydrochloride radical [ 205 ]. In addition, treatment with curcumin (10 μM) decreases oxidation-associated protein modification including carbonylation and nitrotyrosine formation to rescue dopaminergic cells [ 106 ]. Curcumin effectively protects mitochondria from oxidative stress-associated damage [ 206 ].…”
Section: Polyphenolsmentioning
confidence: 99%
“…A new potential protective effect of curcumin on dopamine neurons is the regulation of autophagy, by decreasing the BAX/BCL2 ratio and increasing of LC3 and ATG10 expression (two factors involved in the formation of autophagosome) (273), by regulation of TFEB export signaling via inhibition of glycogen synthase kinase-3b (GSK-3b) (234), and by activation of autophagy in an ROS-dependent manner (255). Some authors demonstrated a key role of curcumin in reducing oxidative stress, for example lowering the level of ROS (274) and oxidized proteins (275), and through modulation of the NRF-2/HO-1 pathway (234). Furthermore, curcumin prevented the LPS-induced upregulation of the protein activity of NF-κB, proinflammatory cytokines (TNF-α, IL-1β, and IL-1α), and inducible nitric oxide synthase (iNOS).…”
Section: Parkinson Diseasementioning
confidence: 99%